Whole Genome-Based Characterization of Listeria monocytogenes Isolates Recovered From the Food Chain in South Africa - Mafuna, Thendo; Matle, Itumeleng; Magwedere, Kudakwashe; Pierneef, Rian E.; Reva, Oleg N. (Frontiers in Microbiology, 2021)
Listeria monocytogenes is an important foodborne pathogen which has the ability to adapt and survive in food and food processing facilities where it can persist for years. In this study, a total of 143 L. monocytogenes isolates in South Africa (SA) were characterized for their strain’s genetic relatedness, virulence profiles, stress tolerance and resistance genes associated with L. monocytogenes. The Core Genome Multilocus Sequence Typing (cgMLST) analysis revealed that the most frequent serogroups were IVb and IIa; Sequence Types (ST) were ST204, ST2, and ST1; and Clonal Complexes (CC) were CC204, CC1, and CC2. Examination of genes involved in adaptation and survival of L. monocytogenes in SA showed that ST1, ST2, ST121, ST204, and ST321 are well adapted in food processing environments due to the significant over-representation of Benzalkonium chloride (BC) resistance genes (bcrABC cassette, ermC, mdrL and Ide), stress tolerance genes (SSI-1 and SSI-2), Prophage (φ) profiles (LP_101, vB LmoS 188, vB_LmoS_293, and B054 phage), plasmids profiles (N1-011A, J1776, and pLM5578) and biofilm formation associated genes. Furthermore, the L. monocytogenes strains that showed hyper-virulent potential were ST1, ST2 and ST204, and hypo-virulent were ST121 and ST321 because of the presence and absence of major virulence factors such as LIPI-1, LIPI-3, LIPI-4 and the internalin gene family members including inlABCEFJ. The information provided in this study revealed that hyper-virulent strains ST1, ST2, and ST204 could present a major public health risk due to their association with meat products and food processing environments in SA.